Concrete crack identification method based on ettringite radiography

By generating ettringite in concrete as a tracer and combining tomography technology, accurate identification and non-destructive detection of concrete cracks are achieved, and the problems of difficulty in identifying cracks at small and medium-sized scales and sample damage are solved in the prior art.

CN119915849APending Publication Date: 2025-05-02NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510166312.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing concrete crack detection technology is difficult to accurately identify small-scale cracks, and traditional methods are prone to damage samples during the inspection process, resulting in inaccurate results.

Method used

By ettringle contrast, the concrete sample is placed in the power-on device and the electrochemical reaction of sulfate and alkali metal solution is used to generate ettringle, and tomography is performed as a tracer to obtain the crack distribution on the surface of the concrete sample.

Benefits of technology

This method can non-destructively obtain the crack distribution inside concrete, improve the recognizable cracks, overcome the resolution limitations and sample damage problems of traditional methods, and make the results more accurate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119915849A_ABST
    Figure CN119915849A_ABST
Patent Text Reader

Abstract

The invention relates to a concrete crack identification method based on ettringite radiography. Comprising the following steps: (1) preparing a water-saturated concrete sample; (2) placing the water-saturated concrete sample in a concrete electrifying device, connecting one surface of the water-saturated concrete sample containing the crack with a sulfate solution, connecting the opposite surface with an alkali metal solution, leading out a wire from a container containing the sulfate solution and the alkali metal solution to the positive and negative electrodes of a direct-current power supply, switching on the power supply, driving sulfate ions to immerse into the concrete sample, and electrifying the concrete sample; the ettringite is generated; (3) removing the electrifying device, and putting the sample into a weak acid solution to corrode the sample; and (4) sealing the surface of the sample by using a fixing agent, carrying out tomography imaging, and obtaining the crack distribution on the surface of the concrete sample by using ettringite as a tracer agent. After the concrete framework rich in calcium ions is combined with a developing solution rich in sulfate, secondary ettringite can be generated to serve as a tracer agent, and the recognizable degree of cracks in concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building material characterization, and in particular relates to a concrete crack identification method based on ettringite angiography. Background Art

[0002] The importance of concrete crack identification cannot be ignored. It is not only a destruction of the integrity of the structure's appearance, but also a potential warning of reduced bearing capacity and durability of concrete. As a composite material widely used in the construction field, the durability of concrete is directly related to the service life and safety and reliability of the structure. The appearance of cracks provides an intrusion channel for corrosive media such as moisture, air, and chemicals, accelerating the deterioration process inside the concrete.

[0003] From a mechanical point of view, the impact of cracks on concrete performance is particularly significant. The existence of cracks destroys the stress balance state inside the concrete, causing the originally evenly distributed load to become concentrated, resulting in a sudden increase in stress in local areas, which can easily lead to further damage to the structure. More seriously, the exposure of cracks allows the steel bars in the concrete to come into direct contact with the external environment. Under humid and aerobic conditions, the steel bars are prone to rust, which not only weakens the strength of the steel bars themselves, but also greatly reduces the bonding force between the steel bars and concrete, thereby seriously weakening the overall bearing capacity of the structure.

[0004] In addition, cracks also exacerbate the durability issues of concrete, such as freeze-thaw cycles, carbonation, and chloride ion erosion. During the freeze-thaw cycle, the water in the cracks expands and contracts continuously when freezing and melting, further widening the cracks and forming a vicious cycle; carbonation reduces the alkaline environment of concrete and destroys its internal microstructure; chloride ion erosion accelerates the corrosion process of steel bars, further weakening the mechanical properties of the structure.

[0005] In recent years, the detection technology of concrete cracks has made significant progress, which can be roughly summarized into two categories: destructive testing technology and non-destructive testing technology. In terms of destructive testing technology, it mainly covers a variety of methods such as steel needle flaw detection method, crack standard width plate combined with feeler gauge method, core drilling method, etc. Among them, the steel needle flaw detection method is famous for its accurate and reliable results, but it will inevitably cause a certain degree of damage to the crack structure of the test sample; the crack standard width plate and feeler gauge method are simple and easy to operate, but their accuracy is relatively low, and they are mainly suitable for measuring large crack widths; the core drilling method can intuitively display the crack situation, but it will also destroy the original crack structure of the sample. In addition, although the microscope method has extremely high accuracy, its sample preparation process is relatively complicated, and steps such as grinding and drying may destroy the original crack structure of the sample, and only the crack information on the surface of the sample can be obtained. In terms of non-destructive testing technology, it mainly includes visual inspection method, infrared thermal imaging method, X-ray tomography imaging method and other methods. The visual inspection method is easy to operate, but is easily affected by subjective factors; the ultrasonic flaw detection method is accurate, but is restricted by multiple factors such as concrete material and structural shape, and it is difficult to accurately determine the three-dimensional distribution of cracks in concrete; infrared thermal imaging can also be used for crack detection, but it is affected by factors such as ambient temperature and emissivity, and its accuracy is limited; X-ray tomography (CT) has low pretreatment requirements for test samples and can accurately obtain three-dimensional distribution information of cracks, but it is limited by the resolution of CT and it is difficult to detect small-scale cracks.

[0006] In recent years, with the continuous development of contrast enhancement technology, X-ray tomography based on contrast enhancement has gradually been widely used. Compared with the traditional CT detection method, this method effectively expands the crack recognition range of CT by enhancing the crack tissue through contrast enhancement technology. However, although this method has improved the recognition effect of crack images to a certain extent, its improvement effect still needs to be further improved. Summary of the invention

[0007] The purpose of the present invention is to provide a method for identifying concrete cracks based on ettringite imaging. Since the concrete skeleton rich in calcium ions can generate secondary ettringite after combining with a developing solution rich in sulfate, this high-density reaction product can fill the gaps in the concrete and resist dissolution, thereby serving as a tracer to improve the recognizability of cracks in the concrete.

[0008] The technical solution to achieve the purpose of the present invention is: a method for identifying concrete cracks based on ettringite imaging, comprising the following steps:

[0009] Step (1): preparing a water-saturated concrete specimen;

[0010] Step (2): placing the water-saturated concrete sample prepared in step (1) in a concrete electrification device, wherein one side of the water-saturated concrete sample including a crack is connected to a sulfate solution, and the other side is connected to an alkali metal solution, and wires are connected from containers containing the sulfate solution and the alkali metal solution to the positive and negative electrodes of a direct current power supply, and the power supply is turned on to drive sulfate ions to penetrate into the concrete sample to generate ettringite;

[0011] Step (3): remove the energizing device and place the sample in a weak acid solution to dissolve the sample;

[0012] Step (4): The sample surface is sealed with a fixing agent, and tomography imaging is performed, using ettringite as a tracer to obtain the crack distribution on the surface of the concrete sample.

[0013] Furthermore, step (1) is specifically as follows:

[0014] Step (11): placing the concrete sample to be analyzed into a drying dish and immersing the sample in deionized water several times the volume of the concrete;

[0015] Step (12): Use a vacuum pump connected to a drying dish to evacuate the sample until the weight of the sample no longer changes.

[0016] Furthermore, the sulfate solution in step (2) is one or more of sodium sulfate and potassium sulfate solutions, and the alkali metal solution is one or more of sodium hydroxide and potassium hydroxide.

[0017] Furthermore, in step (2), the volumes of the sulfate solution and the alkali metal solution are both more than 6 times the volume of the concrete sample.

[0018] Furthermore, in step (2), the concentration of the sulfate solution is 6 mol / L, and the concentration of the alkali metal solution is 6 mol / L; and the liquid levels of the sulfate solution and the alkali metal solution are kept consistent during the power-on process.

[0019] Furthermore, in step (3), the sample is placed in a 1 mol / L ammonium chloride solution or ammonium nitrate solution and immersed for more than 14 days.

[0020] Furthermore, the fixing agent used in step (4) is epoxy resin or paraffin.

[0021] Furthermore, in step (4), tomographic imaging is performed using X-rays, neutron rays or gamma rays.

[0022] Furthermore, in step (4), the image obtained by tomographic imaging is threshold segmented, and according to the grayscale of ettringite, ettringite in the cracks is extracted for three-dimensional reconstruction, thereby obtaining the crack distribution on the surface of the concrete sample.

[0023] Compared with the prior art, the present invention has the following significant advantages:

[0024] 1. Compared with traditional crack testing methods such as visual inspection and scanning electron microscopy, this method can obtain the crack distribution inside the sample without cutting the sample surface, so it will not introduce new cracks, and the results are non-destructive and more accurate.

[0025] 2. Compared with the direct use of tomography imaging technology, this method uses calcium sulfide to improve the linear absorption coefficient of the crack, thereby improving the crack contrast and overcoming the resolution limitation of traditional tomography technology.

[0026] 3. Compared with the previous contrast-tomography combined technology, the contrast agent used in this method does not have high contrast itself. Only after reacting with concrete and depositing in the cracks will it cause a local increase in contrast. Therefore, the contrast is more targeted.

[0027] 4. This method utilizes the difficult dissolution characteristics of calcium aluminate to amplify the contrast difference between the crack and the concrete matrix, providing convenience for the final acquisition of the crack distribution and is highly targeted. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a crack identification flow chart of the present invention.

[0029] Figure 2 This is a reconstruction image of a typical sample before dissolution of the present invention.

[0030] Figure 3 This is a reconstruction image of a typical sample after dissolution obtained after being treated by the present invention.

[0031] Figure 4 This is the extracted crack distribution result after being processed by the present invention. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0033] A concrete crack identification method based on ettringite imaging comprises the following steps:

[0034] Step (1): Take a volume V of concrete to be analyzed and put it into a drying dish, immerse the sample in deionized water; connect the drying dish with a vacuum pump and evacuate until the weight of the sample no longer changes;

[0035] Step (2): When the mass of the sample no longer changes, take saturated concrete, including a soluble sulfate solution with a volume several times V on one side of the crack and an alkali metal solution with a volume several times V on the other side;

[0036] Step (3): Use sulfate solution and alkali metal solution as cathode and anode respectively, apply electricity for several hours to accelerate the penetration of sulfate ions into the concrete; the reaction occurs as follows:

[0037]

[0038] 3CaO·Al2O3(C3A)+33CaSO4·2H2O+26H2O→3CaO·Al2O3·3CaSO4·32H2O

[0039] Step (4): Remove the power supply device and place the sample in a weak acid solution to promote sample dissolution; the reaction is as follows:

[0040] Ca(OH)2→Ca 2+ +2OH -

[0041] Step (5): Use a fixing agent to seal the sample surface, then take the concrete to carry out tomographic imaging analysis, use calcium sulfate with a high linear absorption coefficient as a tracer, and obtain the crack distribution on the concrete surface.

[0042] The sulfate solution in step (2) can be one or more of sodium sulfate and potassium sulfate solutions, and the alkali metal solution can be one or more of sodium hydroxide and potassium hydroxide.

[0043] In step (2), the volume of the conductive solution is more than 6 times the volume of the concrete.

[0044] The conduction time in step (3) is 2-4 hours, which drives sulfate ions to penetrate into the interior and generates calcium sulfonate in the cracks.

[0045] The weak acid solution in which the sample is immersed in step (4) is an ammonium chloride solution or an ammonium nitrate solution.

[0046] The tomography imaging of step (5) includes X-ray, neutron ray, gamma ray tomography imaging, etc.

[0047] The fixing agent in step (5) can be epoxy resin, paraffin, etc.

[0048] Example

[0049] The present invention discloses a concrete crack identification method based on ettringite imaging. Specifically:

[0050] Step (1): Place the concrete to be analyzed into a drying dish and immerse the sample in deionized water 6 times the volume of the concrete;

[0051] Step (2): Use a vacuum pump connected to a drying dish to evacuate the sample for 48 hours until the weight of the sample no longer changes;

[0052] Step (3): Prepare a concrete conductive accelerator (see Figure 1). Inject 1L of 6mol / L sodium sulfate solution and 1L of 6mol / L sodium hydroxide solution into the container respectively. Connect the lead wires of the container containing sodium sulfate solution and sodium hydroxide solution to the positive and negative poles of a 60V DC power supply respectively, and turn on the power for 2h. During the power-on process, pay attention to the solution level in the container and replenish the solution in time.

[0053] Step (4): Take out the sample from the energized device and immerse the concrete sample in 1L of 1mol / L ammonium chloride solution for more than 14 days. The reconstructed image of the sample is as follows: Figure 2 Shown

[0054] Step (5): Use running water to flush away the residual solution on the concrete surface. After the surface is dry, use epoxy resin to seal the sample surface.

[0055] Step (6): After the resin is completely hardened, take the sample for X-ray tomography imaging analysis. The instrument used is Carl Zeiss's Xradia 515Versa micro-computed tomography system, with an X-ray energy of 100 KeV, a scanning time of 1 hour, and an effective resolution of 12 μm. The typical image obtained is as follows: Figure 3 shown.

[0056] Step (7): Using threshold segmentation, according to the grayscale of ettringite, extract the ettringite in the cracks for three-dimensional reconstruction. The typical image obtained is as follows: Figure 4 shown.

[0057] As can be seen from the figure, the concrete skeleton is dissolved, while the ettringite filling the cracks is preserved, thereby reflecting the crack morphology in the concrete. This proves that the present invention is accurate and effective.

Claims

1. A method for identifying concrete cracks based on ettringite imaging, characterized in that: The steps include: Step (1): preparing a water-saturated concrete specimen; Step (2): placing the water-saturated concrete sample prepared in step (1) in a concrete electrification device, wherein one side of the water-saturated concrete sample including a crack is connected to a sulfate solution, and the other side is connected to an alkali metal solution, and wires are connected from containers containing the sulfate solution and the alkali metal solution to the positive and negative electrodes of a direct current power supply, and the power supply is turned on to drive sulfate ions to penetrate into the concrete sample to generate ettringite; Step (3): remove the energizing device and place the sample in a weak acid solution to dissolve the sample; Step (4): The sample surface is sealed with a fixing agent, and tomography imaging is performed, using ettringite as a tracer to obtain the crack distribution on the surface of the concrete sample.

2. The method according to claim 1, characterized in that: Step (1) is specifically as follows: Step (11): placing the concrete sample to be analyzed into a drying dish and immersing the sample in deionized water several times the volume of the concrete; Step (12): Use a vacuum pump connected to a drying dish to evacuate the sample until the weight of the sample no longer changes.

3. The method according to claim 2, characterized in that The sulfate solution in step (2) is one or more of sodium sulfate and potassium sulfate solutions, and the alkali metal solution is one or more of sodium hydroxide and potassium hydroxide.

4. The method according to claim 3, characterized in that In step (2), the volumes of the sulfate solution and the alkali metal solution are both more than 6 times the volume of the concrete sample.

5. The method according to claim 4, characterized in that In step (2), the concentration of the sulfate solution is 6 mol / L, and the concentration of the alkali metal solution is 6 mol / L; and the liquid levels of the sulfate solution and the alkali metal solution are kept consistent during the power-on process.

6. The method according to claim 5, characterized in that In step (3), the sample is placed in a 1 mol / L ammonium chloride solution or ammonium nitrate solution and immersed for more than 14 days.

7. The method according to claim 1, characterized in that The fixing agent used in step (4) is epoxy resin or paraffin.

8. The method according to claim 1, characterized in that In step (4), tomographic imaging is performed using X-rays, neutron rays or gamma rays.

9. The method according to claim 7, characterized in that: Step (4) of tomography imaging The obtained image is segmented by threshold value, and according to the grayscale of ettringite, the ettringite in the crack is extracted for three-dimensional reconstruction. Thus, the crack distribution on the surface of the concrete specimen is obtained.